Facilitators and barriers of adherence to rectal interventions by parents of young children with functional constipation: a qualitative study - Shen, Haiyan; Zhang, Li; Zhang, Yu; Huang, Yan; Xu, Banghong; Yu, Mingming (Frontiers in Pediatrics, 2024)
Background: Functional constipation in children is a worldwide problem that impacts both children's gastrointestinal function and the quality of family life. The treatment of this condition often depends on parental involvement to administer rectal interventions to their children to stimulate defecation. However, adherence to rectal interventions is currently suboptimal. We sought to explore the factors that facilitate and hinder parents from adherence to rectal interventions. Methods: A descriptive qualitative study was conducted involving semi-structured interviews with parents of infants and young children with functional constipation requiring rectal interventions from March to May 2023. The data were analyzed using content analysis. Results: Fourteen parents participated in the study. Parents reported the main facilitators of adherence to prescribed rectal interventions as recognition of illness severity, support from family and friends, and medical resource support and e-health literacy. Parents reported the primary barriers as information barriers, family conflict, cognitive misalignment, and difficulties in accessing healthcare services. Conclusion: Rectal interventions are often essential in managing constipation in young children, with parental compliance being crucial for effective treatment. Healthcare providers must consider the psychosocial aspects of parents' perceptions, adhere to guidelines to standardize communication, and ensure comprehensive education to improve medication literacy.